Assessing collapse safety of CBF buildings subjected to crustal and subduction earthquakes. (December 2015) - Tirca, Lucia; Chen, Liang; Tremblay, Robert
Abstract: The study described in this paper investigated the effects of a mega-thrust subduction earthquake on the seismic performance of moderately ductile concentrically braced frame multi-storey office buildings (MD–CBF) located on Site Class C in Victoria, B.C., Canada. Using data from the 2011 Mw 9 Tohoku subduction earthquake in Japan and worldwide crustal earthquakes, nonlinear dynamic analyses were performed on detailed numerical models developed in the OpenSees framework. It was found that the effect of Trifunac duration on the nonlinear seismic response of 4-storey, 8-storey and 12-storey MD–CBF office buildings is particularly significant in terms of the strain accumulated in the fibers of hollow structural section braces causing low-cycle fatigue fracture. In addition, assessment of the likelihood of collapse safety of the studied multi-storey MD–CBF buildings found that the collapse margin ratio ( CMR ) value and the adjusted collapse margin ratio ( ACMR ) value are approximately 150% greater under the crustal record set than under the subduction record set. Among the three buildings studied, only the 12-storey MD–CBF building subjected to the subduction record set failed to meet the collapse safety criterion of ACMR  >  ACMR 10% . Consequently, the CMR value needs to be increased by strengthening the structural system. Therefore, particular attention should be given when designing MD–CBF multi-storey buildings located in the proximity of subduction fault, such as buildings in Victoria that lie within the Cascadia subduction zone. Highlights: Subduction records suitable for Victoria BC were selected from Mw 9 Tohoku earthquake. The 12-st. CBF building didn't meet the collapse safety criterion under subduction records. Duration of subduction records impacts the accumulated strain in HSS brace fibers. Underestimated braces' overstrength could lead multi-storey CBF buildings to failure.